The Geography of Hedge Funds - TEO, Melvyn (Institutional Knowledge at Singapore Management University, 2009)
This article analyzes the relationship between the risk-adjusted performance of hedge funds and their proximity to investments using data on Asia-focused hedge funds. I find, relative to an augmented Fung and Hsieh (2004) factor model, that hedge funds with a physical presence (head or research office) in their investment region outperform other hedge funds by 3.72% per year. The local information advantage is pervasive across all major geographical regions, but is strongest for emerging market funds and funds holding illiquid securities. These results are robust to adjustments for fund fees, serial correlation, backfill bias, and incubation bias. I show also that distant funds, especially those based in the United States and the United Kingdom, are able to raise more capital, charge higher fees, and set longer redemption periods, despite their underperformance relative to nearby funds. It appears that distant funds trade investment performance for better access to capital.